Drivers of Firm Value: Evidence from Green Accounting, Audit Signals, and Financial Performance - Christian, Feivel Vito; Rinendy, Jhon; Pangaribuan, Hisar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This study examines the drivers of firm value by analyzing the effects of Green Accounting, Financial-Risk Assurance, Audit Timeliness, Leverage, and Profitability among companies listed in the LQ45 Index in Indonesia during 2020–2024. Using panel data regression on 125 firm-year observations, the results indicate that Green Accounting practices and profitability have a positive and significant impact on firm value, suggesting that capital markets reward both environmental commitment and strong financial performance. In contrast, higher Financial-Risk Assurance, longer audit delays, and greater leverage are associated with lower firm value, reflecting negative market perceptions of risk exposure, reporting inefficiency, and financial pressure. Overall, the findings demonstrate that firm value is influenced by an integrated set of sustainability, audit, and financial signals rather than by profitability alone. This study underscores the importance of credible sustainability disclosure, timely auditing, and sound financial structure in supporting transparency and signalling theories, which also enhance firm value within Indonesia’s capital market.